Biomechanical Principles of Spinal Deformity Correction in the Thoracolumbar Spine - Shaw, K Aaron; O'Sullivan, Michael; Wang, Xiaoyu; Aubin, Carl-Eric (Journal of the American Academy of Orthopaedic Surgeons, 2025)
Thoracolumbar spinal deformities are a pervasive condition affecting the adolescent and adult patient population. These deformities represent three-dimensional alterations in the coronal, sagittal, and transverse planes with implication on the local, regional, and global alignment. With continued studies, the importance of the overall correction on long-term outcomes has been established. Surgical techniques for correcting deformities aim to restore coronal and sagittal alignment of the spine, as well as manage the rotational components in the transverse plane. Through a proper understanding of spinal biomechanics and spinal instrumentation, we can gain better understanding of how to harness the biomechanical properties of the spinal anatomy through the application of deformity correction techniques to optimize the three-dimensional correction of spinal deformities.